Quality of telework life, job crafting, and work well-being of public school teachers in the Federal District - Paschoal, Tatiane; Silva, Priscila Maria da; Demo, Gisela; Fogaça, Natasha; Ferreira, Mario Cesar (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
This study tested the impacts of perceptions of quality of telework life and job crafting on public school teachers’ work well-being. The sample was composed of 184 teachers who answered a questionnaire with scales previously validated in Brazil. Confirmatory factor analysis and structural equation modeling were performed. Perceptions of quality of telework life and job crafting actions predicted work well-being and contributed to investigating gaps in the organizational and work literature. This study offers a diagnosis of teachers’ experiences during remote work and highlights the relations between those variables in a changing work context transformation, fostered by Covid-19 pandemia.